Relationship between Helicobacter pylori infection and visceral fat area in diabetic populations: the mediating role of insulin resistance - Chen, Yi; Ni, Bingqian; You, Ningning; Chen, Yahong; Zhang, Jinshun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundObesity has become a global health concern, particularly in relation to abdominal fat which is associated with various diseases. The connection between Helicobacter pylori (H. pylori) and obesity is still debated, with limited research on the link between H. pylori and visceral fat. This study aimed to examine the correlation between H. pylori infection and visceral fat area (VFA) among participants.MethodsA total of 18,076 individuals participated in this study, undergoing assessments of VFA, physical parameter measurements, and serum examinations. Bioelectrical impedance was used to analyze VFA, with the triglyceride-glucose (TyG) index indicating levels of insulin resistance (IR) in the population. Multiple linear regression analysis was utilized to determine the factors influencing VFA, while a generalized additive model was employed to assess potential non-linear associations between the TyG index and VFA.ResultsH. pylori was recognized as a contributing factor to VFA exclusively within diabetic populations. In these populations, a significant nonlinear relationship existed between the TyG index and VFA. Furthermore, mediation analysis indicated that the TyG index acted as a mediator in the relationship between H. pylori and VFA.ConclusionH. pylori is closely associated with VFA in individuals with diabetes, with IR serving as a mediating factor in the relationship between H. pylori and VFA.